Preperation of activated Carbon by chemical treatment and effect of GAMMA radiation on it - Ammar Hamdoon; Khaled Awaid; Safwan Ali (College of Education for Pure Sciences, 2005)
In this work activated carbon of a good quality was prepared using oxidation condensation process, The oxidation of the asphaltic materials was conducted using 2% by weight of FeCb and in the presence of a strea:n of air. The reaction mixture was heated at 350:C for 3hrs, followed by removal of uncarbonized material tinder reduced pressure. The condensed fraction obtained is expected to recombine or re-react to give a high carbon content. The carbonized was conducted at 550±25°C for 3hrs and the ratio of the feedstock to KOH was (1:2), alter the carboni/ation the reaction mixture was subjected to purification by treatment with 10% HCI under reflux .for 1 hr. filtrated and then washed by distilled water till it give neutral test litmus paper. The sample was dried at 120'C for 24hr and its physical properties were determined. Their: the samples (prepared & commercial) were irradiated at room temperature using different times of irradiations. The physical properties for activated carbon were determined in order to know effect of gamma irradiation. الخلاصة